Unfolding Industrial Output: A Study of India’s Formal Manufacturing Sector - Choudhry, Sonam (Unisia, 2022)
Investigation of economic development and growth has been at the forefront of economic research (Denison 1962; Barro 1996). The idea of focusing on the industrial sector to drive economic growth has been a global phenomenon. The process of economic growth has been supplemented with several structural changes that an economy goes through. The mainstream literature predicts that the opening up of the economy increases the exports of commodities based on the economy’s comparative advantage. One of the principal questions that the paper attempts is to examine whether the openness of the Indian economy resulted in the expansion of the share of export-oriented industries and the reduction of import-competing industries' share in manufacturing output. The analysis uses rich granular-level data on the Indian formal manufacturing sector. Furthermore, the analysis of structural changes requires looking not only at the growth rate over a particular period but also at the cumulative increase in growth of the sector according to different activities which may be labour or capital-intensive. The paper using cluster-based analysis decomposes manufacturing growth into labour and capital-intensive activities and brings out important aspects on how the manufacturing output is been produced. The pattern of capital intensity of Indian manufacturing firms shows that firms have systematically witnessed an increase in capital intensity. Factors such as incentives in the form of subsidies, and reduction in tariffs on capital goods made access easier to adopt advanced technology. Also in today’s globalised world, the pressure on domestic firms to remain competitive both in the external and domestic markets created grounds for adopting the latest (more capital-intensive) techniques.